2022
DOI: 10.3390/fishes7050222
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Selectivity of Ruditapes philippinarum on Phytoplankton

Abstract: A monthly survey of the feeding selectivity of Ruditapes philippinarum in the Yalu River Estuary in 2020–2021 was conducted using high-throughput sequencing identification and visual grading technology. The results showed that the most-dominant species in the water of the shellfish culture area and in the stomachs of R. philippinarum was Karlodinium veneficum in those years. The selectivity index (E) indicated that R. philippinarum avoided consuming Bacillariophyta, Chrysophyta and Cryptophyta throughout the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In the case of electropolymerization of DA in the absence of OR , the voltammetric response was very similar to that obtained in the presence of OR (Figure 2B). This result reveals that the electropolymerization of DA was not affected by the template molecule which is electro‐inactive in the applied potential range [46].…”
Section: Resultsmentioning
confidence: 82%
“…In the case of electropolymerization of DA in the absence of OR , the voltammetric response was very similar to that obtained in the presence of OR (Figure 2B). This result reveals that the electropolymerization of DA was not affected by the template molecule which is electro‐inactive in the applied potential range [46].…”
Section: Resultsmentioning
confidence: 82%
“…Environmental factors affecting the size-class composition of microalgal phytoplankton are complex, and for near-shore waters, nutrient salt concentration and structure have the greatest impact (Liu et al, 2022b). Larger-sized phytoplankton dominate eutrophic waters, while smaller-sized phytoplankton are better adapted to nutrient-poor waters (Deng et al, 2008;Huang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…and Cyclotella sp. Many studies have indicated that predominant marine phytoplankton size is decreasing (Liu et al, 2022b;Edwards and Richardson, 2004;Lundholm et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation